Comprehensive Genetic Results for Primary Immunodeficiency Disorders in a Highly Consanguineous Population - Al-Herz, Waleed; Chou, Janet; Delmonte, Ottavia Maria; Massaad, Michel J.; Bainter, Wayne; Castagnoli, Riccardo; Klein, Christoph; Bryceson, Yenan T.; Geha, Raif S.; Notarangelo, Luigi D. (Frontiers in Immunology, 2019)
Objective: To present the genetic causes of patients with primary immune deficiencies (PIDs) in Kuwait between 2004 and 2017. Methods: The data was obtained from the Kuwait National Primary Immunodeficiency Disorders Registry. Genomic DNA from patients with clinical and immunological features of PID was sequenced using Sanger sequencing (SS), next generation sequencing (NGS) of targeted genes, whole exome sequencing (WES), and/or whole genome sequencing (WGS). Functional assays were utilized to assess the biologic effect of identified variants. Fluorescence in situ hybridization (FISH) for 22q11.2 deletion and genomic hybridizations arrays were performed when thymic defects were suspected. Results: A total of 264 patients were registered during the study period with predominance of patients affected with immunodeficiencies affecting cellular and humoral immunity (35.2%), followed by combined immunodeficiencies with associated syndromic features (24%). Parental consanguinity and family history suggestive of PID were reported in 213 (81%) and 145 patients (55%), respectively. 206 patients underwent genetic testing with a diagnostic yield of 70%. Mutations were identified in 46 different genes and more than 90% of the reported genetic defects were transmitted by AR pattern. The majority of the mutations were missense mutations (57%) followed by frame shift mutations. Five novel disease-causing genes were discovered. Conclusions: Genetic testing should be an integral part in the management of primary immunodeficiency patients. This will help the delivery of precision medicine and facilitate proper genetic counseling. Studying inbred populations using sophisticated diagnostic methods can allow better understanding of the genetics of primary immunodeficiency disorders.